New mitogenomes from the genus Cricotopus (Diptera: Chironomidae, Orthocladiinae): Characterization and phylogenetic implications - Li, Shu‐Yi; Chen, Meng‐Han; Sun, Li; Wang, Rui‐Hao; Li, Chen‐Hong; Gresens, Susan; Li, Zhao; Lin, Xiao‐Long (Archives of insect biochemistry and physiology, 2024)
Cricotopus is a large and diverse genus of non‐biting midges composed of several subgenera. Complete mitogenome sequences are available for very few Cricotopus species. The subgenus Pseudocricotopus unites species with unusual morphological structures in adult male and pupal stages, however, molecular methods are needed to verify the placement of this subgenus within Cricotopus. We obtained mitogenomes of C. (Pseudocricotopus) cf. montanus and nine other Cricotopus species for phylogenetic analysis, coupled with two Rheocricotopus species and one Synorthocladius species as outgroups. The structure of the mitogenome was similar among these Cricotopus species, exhibiting A+T bias and retaining ancestral gene order. Mutation rate, estimated as Ka/Ks, varied among genes, and was highest for ATP8 and lowest for COI. The phylogenetic relationships among species of Cricotopus, Rheocricotopus and Synorthocladius was reconstructed using Bayesian inference and maximum likelihood estimation. The phylogenetic trees confirmed placement of subgenus Pseudocricotopus, represented by Cricotopus cf. montanus, within Cricotopus. Our study increases the library of chironomid mitogenomes and provides insight into the properties of their constituent genes. We have sequenced new mitogenomes for nine Cricotopus species, one Rheocricotopus species and one Synorthocladius species. Phylogenies showed that the subgenus Pseudocricotopus does belong within the genus Cricotopus. Research highlights We sequenced new mitogenomes for nine Cricotopus species, one Rheocricotopus species and one Synorthocladius species. Comparative analysis of mitogenome structure showed that nucleotide composition and gene order of these Cricotopus mitogenome were conservative. Phylogenies showed that the subgenus Pseudocricotopus does belong within the genus Cricotopus.